The Impact of Political Identity on Candidate Electability in Village Head Elections - Misbahuddin, Misbahuddin; Hawing, Hardianto; Muhiddin, Amir (Journal of Contemporary Local Politics, 2023)
This study examines the partial and simultaneous impact of Identity Politics on the Electability of Village Head Candidates in Layoa Village, Gantarang Keke District, Bantaeng Regency. The research used a quantitative approach with descriptive research type. The sampling technique used was saturated sampling with the use of Likert scale instruments, and the data were analyzed using descriptive statistical techniques and simple regression analysis with the help of SPSS software version 26. The results showed that partially, the legitimacy identity indicator (X1) had an impact of 49.9%, resistance identity (X2) of 64.2%, and project identity (X3) had an impact of 66.2% on the electability of Village Head Candidates. The impact is measured through simple regression for each identity indicator. Simultaneously, Political Identity significantly affects the electability of Village Head Candidates, as indicated by the Fcount value of 916.773 with a significance level of 0.000, smaller than 0.05. The magnitude of the variable's impact is measured by the R Square value of 0.908, which means that 90.8% of the variation in electability can be explained by the Identity Politics variable. The remaining 9.2% is attributable to other factors not examined in this study.